Web Information Systems and Mining International Conference, WISM 2012, Chengdu, China, October 26-28, 2012. Proceedings - Wang, Fu Lee (Lecture Notes in Computer Science, 2012)
The volume LNCS 7529 constitutes the refereed proceedings of the International Conference on Web Information Systems and Mining, WISM 2012, held in Chengdu, China, in October 2012. The 87 revised full papers presented were carefully reviewed and selected from 418 submissions. The papers are organized in topical sections on applications of Web information systems; applications of Web mining; e-government and e-commerce; information security; intelligent networked systems; management information systems; mobile computing; semantic Web and ontologies; Web information extraction; Web intelligence; Web interfaces and applications; and XML and semi-structured data.